Lucky - Collins, Jackie (London Pan Books, 1986)
Confessions of a Wild Child: Who is Lucky Saint? She's a fifteen-year-old wild child who discovered her mother's murdered body floating in the family swimming pool when she was only five years old. In Confessions of a Wild Child you will follow Lucky as she navigates her teen years - boys, drugs, family dramas, and many adventures from Greek islands to Vegas penthouses. You will meet the Santangelo family. Gino Santangelo, Lucky's father, a powerful man with a dubious past, who owns hotels in Vegas and struggles to control his willful and stubborn daughter. And Dario, Lucky's gay teenage brother who is too scared to reveal his sexual preference to his father. In Confessions of a Wild Child you will discover how Lucky strikes a path to become the powerful and charismatic woman she is today. Lucky: With the sensual grace of a panther, Lucky Santangelo prowled her Las Vegas casino, restless, ready, eager for action. That night began a dazzling odyssey, filled with dangerous passion and sun-drenched sex, sadistic vengeance and breathless suspense. From the decadent luxury of California, to Paris, New York and a private Greek island, Lucky fought for her father's honour, for ruthless triumph, for the wild card of a fabulous love. Her rivals; an ice-cold Hollywood wife...a much-married heiress strung out on cocaine...a jaded magnate hooked on power...a crazed hoodlum lusting for murder. But Lucky was a gambIer and a lover, a woman who ruled her empire and pursued her man with the potent Santangelo strength...her way, on her terms, whatever the odds. Jackie Collins tops the sensational success of Hollywood Wives and Chances with Lucky, "so hot it will have to be printed on asbestos.
Includes Epilogue
Keywords: Capitalists and Financiers -- Santangelo, Lucky (Fictitious Character)